Microfluidization-Driven Changes in Some Physicochemical Characteristics, Metal/Mineral Composition, and Sensory Attributes of Sugarcane Juice - Ayon Tarafdar; Barjinder Pal Kaur (Journal of Food Quality)
This work evaluated the effect of microfluidization at different pressure (50, 100, 150, and 200 MPa)-cycle (1, 3, 5, 7) combinations on the physicochemical (total soluble solids, titratable acidity, pH, and electrical conductivity), sensory, and metal/mineral composition of sugarcane juice which was previously unexplored. Juice extracted from blanched sugarcane stems (var Co 0238) was microfluidized, and the analysis for different parameters was conducted using standard protocols. The mineral/metal composition was determined using ICP-OES following a wet digestion method. Results showed that TSS decreased from 18.88 °Brix to a range of 10.15–15.7 °Brix with the former (lower value) being due to the release of insoluble matter after microfluidization which was further solubilised at higher processing cycles (as in the latter). The pH did not vary significantly as compared to control and was in the range of 5.2–5.7. However, a decrease in titratable acidity (0.1–0.26%) was found as compared to control (0.26%). The electrical conductivity of microfluidized sugarcane juice varied from 4.45 to 5.12 mS as compared to 4.95 mS for control. Metal/mineral analysis showed rich reserves of magnesium, phosphorus, potassium, and calcium in sugarcane juice which degraded after microfluidization perhaps due to filtration effect caused by the micropore in the interaction chamber of the microfluidizer. The sensory score showed acceptability of the juice after microfluidization (overall acceptability ∼7).